2013
DOI: 10.1080/14634988.2013.851592
|View full text |Cite
|
Sign up to set email alerts
|

Fish diversity, community structure and ecological integrity of the tropical River Ganges, India

Abstract: The Ganges River is one of the largest river systems in the world and sustains a rich biodiversity of fish and fishers. In recent years, a decline in fish diversity and catch has become apparent due to various anthropogenic activities in the river basin. This study analyses the current fish diversity, distribution and community structure along the longitudinal gradient of the river and evaluates the ecological integrity of the riverine stretch applying a multimetric assessment approach. One hundred forty three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 21 publications
3
29
0
Order By: Relevance
“…Flow regulation and alteration by dams and barrages, pollution and overfishing of spawn have been unequivocally identified as the major drivers of fishery declines by many studies (Das et al, 2013;Jhingran & Ghosh, 1978;Kelkar, 2014b;Payne et al, 2004;Payne & Temple, 1996;Sarkar et al, 2012;Talwar & Jhingran, 1991). The spatial scale of these studies was basin-wide so flow alterations were identified as the main threat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow regulation and alteration by dams and barrages, pollution and overfishing of spawn have been unequivocally identified as the major drivers of fishery declines by many studies (Das et al, 2013;Jhingran & Ghosh, 1978;Kelkar, 2014b;Payne et al, 2004;Payne & Temple, 1996;Sarkar et al, 2012;Talwar & Jhingran, 1991). The spatial scale of these studies was basin-wide so flow alterations were identified as the main threat.…”
Section: Discussionmentioning
confidence: 99%
“…Fish stocks in the Ganga River have been declining (Das et al, 2013;Payne et al, 2004;Payne & Temple, 1996;Ray, 1998;Sarkar et al, 2012;Vass et al, 2009). In the Ganga River in Bihar, open-access river-floodplain fisheries from 1991 onwards have brought severe conflicts over fishing rights and access to fishing areas.…”
Section: Implications Of Lek For Fisheries Management In the Ganga mentioning
confidence: 99%
“…Orissa constitute about 18.11% to the freshwater fish fauna of India (Dutta et al 1993). Earlier reports on freshwater fish fauna of Odisha such as Hora (1938Hora ( , 1940, Misra (1938), Chauhan (1947), Jayaram and Majumdar (1976), Dutta et al (1993), Ramakrishna et al (2006), Pathak et al (2007), Karmakar et al (2008), Das (2008), Baliarsingh et al (2013), Mishra et al (2013), Singh et al (2013), Behera and Nayak (2014), Satapathy and Misra (2014), Singh (2014), Dandapat (2015), Mohanty et al (2015), Sarkar et al (2015), Das et al (2016) and Samal et al (2016) agreed with dominance of cyprinids over other freshwater fish families. The dominance of cyprinid species in natural water bodies is common all over the South Asia and reported in several studies (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Offline search include offline journals, textbooks, reports and gray literature those are not available online. Pathak et al (2007) River Mahanadi 112 Karmakar et al (2008) Subamarekha River in Mayurbhanj and Baleswar districts 13 Das (2008) Ansupa Lake in Cuttack district 23 Baliarsingh et al (2013) Freshwater bodies from Similipal Biosphere Reserve, Mayurbhanj district 55 Mishra et al (2013) Baitarani River at Jaipur district 25 Singh et al (2013) River Mahanadi 96 Behera and Nayak (2014) Chilika lake in Puri, Khurda and Ganjam districts 14 Satapathy and Misra (2014) River Pilasalunki at Phulbani district 23 Singh (2014) River Mahanadi: Hirakud Reservoir, Satakosia, Kantilo, Banki 56 Dandapat (2015) Samuka River near Sahada Village in Balasore district 10 Mohanty et al (2015) Chilika lake in Puri, Khurda and Ganjam districts 71 Sarkar et al (2015) Ansupa Lake in Cuttack district 28 Das et al (2016) River FIGURE 1 Reported locality of freshwater bodies in Orissa, India (map source: Google Earth)…”
Section: Methodsmentioning
confidence: 99%
“…(2) The Ganges harbours a surprising amount of biodiversity, including the gorgeous Ganges river dolphin, the widely feared Ganges shark, and the awkward-looking gharial crocodile, which can be up to 20 feet in length. (3) Unfor- Self-purifying properties of the Ganges River Scoping Review tunately, many of the interesting animals that inhabit the Ganges are endangered, and many others have long gone extinct.…”
mentioning
confidence: 99%